$\begin{array}{1 1}(A)\;\frac{t_1+t_2}{2} \\(B)\;\frac{t_1-t_2}{2}\\(C)\;t_1+t_2\\(D)\;\sqrt {t_1t_2} \end{array} $

$-h= ut_1- \frac{1}{2}gt_1^2$--------(i)

$h= ut_2+\large\frac{1}{2}$$gt_2^2$--------(ii)

Where h is a positive number. Multiplying (i) by $t_2$ and (ii) by $t_1$ we get,

$h(t_1+t_2)=\large\frac{1}{2}=\large\frac{1}{2} $$gt_1t_2(t_1+t_2)$-----------(iii)

$y= \large\frac{1}{2} $$gt^2$---------(iv)

From (iii) and (iv)

$t= \sqrt {t_1t_2}$

Hence D is the correct answer.

Ask Question

Tag:MathPhyChemBioOther

Take Test

...